The Situation of Mr. Imre Nagy - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. This report describes unconfirmed reports that Mr. Imre Nagy, after leaving the Yugoslav embassy, was transported to Sinaia (Romania) against his will. The Hungarian government refuses to acknowledge this information. The Yugoslav embassy was not informed of this, and is violently protesting to the Hungarian government for violation of agreement.